SHOPEE COLLABORATION WITH AFFILIATES TO CREATE CONSUMER IMPULSE BUYING - Churin In; Risna Nur Ainia; Firza Agung Prakoso (Jurnal Al-fatih Global Mulia, 2023)
One of the platforms developing in Indonesia is "Shopee". Shopee is an online shopping platform that has successfully expanded its market coverage and become one of the leading e-commerce companies in the Southeast Asia region. With the continued growth in the number of users, Shopee provides consumers with access to explore products practically and efficiently. Shopee is not only limited to online business transactions but also creates large and easily accessible job opportunities. One of them is opening an affiliate program by becoming a Shopee content creator. The Shopee affiliate program is a Shopee program for content creators who will promote various products on Shopee for which they will later be given a commission. The more active an affiliate is in promoting Shopee goods, the more commission he will get. This research aims to determine the collaboration between Affiliates and Shopee in encouraging consumers to make unplanned purchases (impulse buying). The method used is a qualitative method with a case study approach. The results of this research show that the Shopee Affiliate program is a collaboration program between Affiliates and Shopee so that Shopee products are better known to the wider community so that Shopee customers continue to increase and this, without realizing it, causes more customers to do impulse buying.